Detection of beta-lactamase production among gram-negative bacteria isolated from semen of male patients with bacteriospermia (2017)
Background: Bacteriospermia, a condition characterized by the presence of bacteria in male ejaculate may influence male infertility. However, presence of bacteria exhibiting resistance to extended-spectrum antibiotics could be a serious challenge to the treatment of bacteriospermia. Objectives: This study examined semen of patients for bacteriospermia and screened for the presence of common beta-lactamases in Gram-negative bacteria isolated, in two teaching hospitals in Oyo State, Nigeria. Methods: Semen samples were collected by masturbation after abstinence for 3 days among 182 male patients attending fertility clinic of Ladoke Akintola University of Technology Teaching Hospital and Bowen University Teaching Hospital between February 2015 and February 2016. Gram-negative bacteria were isolated and identified using standard methods. Antibiotic susceptibility test was by disc-diffusion, beta-lactamase detection by double-disc synergy test and Polymerase Chain Reaction. Results: Bacteriospermia was observed in 26.4% of the patients (age range 21 and 60 years). Escherichia coli, Klebsiella spp., Pseudomonas spp., Entetrobacter spp. and Proteus spp. were isolated. Resistance to amoxicillin, amoxicillin-clavulanate, cefepime, ceftriaxone, cefotaxime, ceftazidime and cefuroxime was observed in 87.5%, 62.5%, 45.8%, 41.7%, 37.5%, 37.5% and 27.1% of the isolates respectively. Resistance to imipenem, ciprofloxacin, ofloxacin and gentamicin was 8.3%, 41.7%, 43.8% and 54.2% respectively. MDR was exhibited by 68.8%. ESBL, AmpC and MBL was produced by 31.3%, 22.9% and 14.6% respectively, with 3(6.3%) co-producing all. bla and bla were detected but AmpC and MBL genes were not. Sequencing revealed bla CTX-M-15 and bla TEM 1 Six of the eight bla CTX-M-15 positive strains lost the gene to mutagenic treatment. Conclusion: High level of MDR bacteria including those producing beta-lactamases in this study calls for caution in the antibiotic treatment of bacteriospermia.